Physiological alteration and the expression of fibrogenesis-proinflammatory genes in hepatocellular carcinoma patients with chronic hepatitis C and onset metabolic syndrome: a preliminary report at Saiful Anwar General Hospital Malang - Hendra Susanto (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2022)
Hepatocellular carcinoma (HCC) is one type of cancer that is included in the fifth order of cancer that causes death in the world. The highest incidence of liver cancer is found in men. Liver function related to the metabolism of various endogenous and exogenous substances is prone to chronic inflammatory stimulation, one of which is hepatitis C virus (HCV) infection. TGF-β1, NOX4, and TNF-α are three potential genes responsible for regulating chronic inflammation and fibrogenesis. This study aims to describe the profile of potential fibrogenesis and inflammation genes that play a role in the progression of HCC due to chronic hepatitis C. This type of research is a descriptive study with a quantitative approach that was carried out using Quantitative Real-Time PCR analysis. The results of serological tests in the male gender group showed that the average fasting body glucose level was 85.22 mg/dL, total cholesterol 242 mg/dL, triglyceride 158.44 mg/dL, HDL-C 18.56 mg/dL, and LDL-C 172 mg/dL. In the female gender group, the data obtained on average levels of fasting blood glucose 82.33l mg.dL, total cholesterol 350 mg/dL, triglyceride 181 mg/dL, HDL-C 29 mg/dL, and LDL-C 190 mg/dL. All gender groups also showed an increase in AST and ALT levels that had exceeded normal limits. The expression of fibrosis-related genes, namely TGF-β1 was 5.8x higher in male patients than female patients. The NOX4 gene also showed almost the same thing, namely, its expression level was 1.2 times higher in male patients. From the expression of the proinflammatory cytokine TNF-, it is also known that in male patients, the expression level is 2x times higher than in female patients. The difference in expression levels in the two groups involved a repressive mechanism of estrogen. Increased expression levels of TGF-β1, NOX4, and TNF- genes are thought to involve the activity of the HCV core protein, which then induces several signaling pathways such as NF-κB and SMAD3. From these results, the expression levels of TGF-β1, NOX4, and TNF- as the main regulators of chronic inflammation and fibrosis can describe the progression of HCC and can be used as initial data on the profile of inflammation and fibrogenesis in HCC cases that have previously been exposed to HCV infection.